Neue Entwicklungen im japanischen Bilanzrecht: Die Reform des Jahres 2003 - Yanaga, Masao (Zeitschrift für Japanisches Recht, 2003)
The latest amendments to the Commercial Code and the Audit Law will have a great influence on the accounting of joint-stock companies, especially ‘large companies’ (yûhô teishutsu dai-kaisha) that should also submit a yûka shôken hôkoku-sho (securities report) to the Prime Minister under the Securities Exchange Law. In line with these amendments, the Enforcement Regulation for the Commercial Code (ERCC) was also revised in February 2003. On the one hand, a yûhô teishutsu dai-kaisha has to prepare consolidated financial statements, which should be audited by the external accounting auditor and the auditors’ board (or audit committee) under the Audit Law. On the other hand, the formal requirements in the ERCC have been harmonized with those for securities regulation purposes. The requirements (mainly terminology) in the ERCC that were incompatible with those in the Financial Statement Regulation (FSR) (for securities regulation purposes) have been amended in harmony with the latter in principle. Moreover, consolidated financial statements prepared in accordance with the Consolidated Financial Statement Regulation (CFSR) (for securities regulation purposes) can fulfill the requirements in the ERCC, which only requires an abridged consolidated balance sheet and an income statement with fewer notes. Furthermore, a yûhô teishutsu dai-kaisha may prepare its financial statements and consolidated financial statements for company law purposes, applying the provisions concerning the terminology and layout in FSR or CFSR. In addition, renketsu keisan shorui sakusei kaisha (companies that fall under certain exceptions with respect to consolidated accounting) may describe some particulars on the group instead of the (parent) company itself in its business report. A Renketsu tokurei kitei tekiyô kaisha will be required to disclose the audit and non-audit fees payable to its external accounting auditor by itself and its consolidated subsidiaries.